Natural Melanin-Based Nanoparticles With Combined Chemo/Photothermal/Photodynamic Effect Induce Immunogenic Cell Death (ICD) on Tumor - Liu, Ding; Huang, Huilin; Zhao, Bingxia; Guo, Weihong (Frontiers in Bioengineering and Biotechnology, 2021)
Melanin, as a natural product, has been used as an extraordinary ingredient for nanomedicine due to its great biocompatibility and light responsive property. In this study, polydopamine (PDA), an analogue of melanin, was extracted from dopamine and encapsulated with doxorubicin (DOX). The as-prepared nanoparticles (NPs) with good stability, great biosafety and high near infrared (NIR) responsive property could ameliorate the cell uptake of DOX in OS-RC-2/ADR cells, exhibit synergistic chemo/photothermal (PTT)/photodynamic (PDT) effect, induce the release of damage associated molecular patterns (DAMPs) and finally lead to immunogenic cell death (ICD). In general, it suggested that PDA-DOX NPs with NIR irradiation could serve as a promising agent for tumor therapy.